Hybrid-Based Verse Connection Method As a Means Of Improving Learning Of Tahfidz Al-Quran - Fachruddin, M. Syauqy; Fahyuni, Eni Fariyatul (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
This study aims to solve problems in the tahfidz class where the hope is that through this verse connection method it can provide a solution to the decline in learning outcomes and students' boredom with traditional methods that have often been practiced so that interest and learning outcomes tahfidz originally decreased to increase, boredom and the absence of students in teaching and learning activities are often a problem in learning, especially tahfidz al qur'an, therefore this research was conducted to provide solutions to the above problems and improve learning outcomes tahfidz al quran, the method used in this research is class action, namely research that directly involves to solve problems that occur in learning, the results of the data obtained average value In the pre-action period 84.11 with a passing percentage of 36%, in cycle 1 the average score of students rose to 68.88 with a passing percentage of 44%, in cycle 2 the average value the average of students rose to 76,89 with a passing percentage of 60,5%, cycle 3 produced an average score of 82,61 with a passing percentage that exceeded the target of 77%. Thus the hybrid learning-based verse connecting method can solve students' boredom and absence problems and improve student learning outcomes in tahfidz learning found in tahfidz class level 3B Mi Baiturrahman, Surabaya